POPULATION DIVERSITY OF XANTHOMONAS ORYZAE PV. ORYZAE CAUSING BACTERIAL LEAF BLIGHT IN RICE FIELDS OF CAN THO - Tuan, Tran Quoc; Hao, Lam Tan; Khoa, Nguyen Dac (Vietnam Journal of Biotechnology, 2018)
Bacterial leaf blight (BB) caused by Xanthomonas oryzae pv. oryzae (Xoo) is a destructive disease in rice fields. Can Tho is one of the most important rice-growing areas in the Mekong Delta, which is vulnerable to climate change, making the disease more damaging in this region. Deployment of resistance genes is considered an economic and eco-friendly approach to control the disease. However, Xoo exists in different races with diverse reactions on different resistance genes. Thus, for effective management of BB, it is essential to understand the diversity of contemporary Xoo population to deploy appropriate resistance genes in rice fields. This study aims at assessing the Xoo population diversity (race composition) in rice fields of Can Tho using pathogenicity reactions on the near-isogenic lines (pathotypes) in combination with insertion sequence-PCR technique using J3 primer (genotypes). Among 132 isolates obtained from BB-infected leaf samples collected from six rice-growing areas of Can Tho, 126 isolates were identified as Xoo using PCR with the specific primers XOO290F/R. The contemporary Xoo population in Can Tho was composed of four races including two classic standard races (5 and 7) and two newly emerged ones (5* and 5**) of which races 5 and 5* were the most predominant. Seven haplotypes were identified in the four races and haplotypes I and III were predominant, accounting for 50.79% and 40.48%, respectively. The combination of the pathotypic and genotypic analyses showed genetic variations in races 5 and 5*. These results could be used for deployment of appropriate BB resistance cultivars in rice fields of Can Tho.